Pelatihan Etika Komunikasi Islam di Zoom Meeting pada Siswa/i SMK Hasanuddin Medan - Nurul Saniah; Indah Lestari (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2022)
This Islamic communication ethics training aims to provide knowledge to students of SMK Hasanuddin Medan that in using the Zoom Meeting application one must have good ethics to other Zoom participants. Ethical practices such as not talking while zooming in, not eating and drinking, lying down, and so on. The method used in this community service is the PAR (Participatory Action Research) method. After delivering the material and training directly so that students of SMK Hasanuddin Medan can use good Islamic communication ethics when attending Zoom Meetings.